Kedudukan Upaya Administratif dalam Dismissal Process dan Konstruksi Ideal Pemeriksaan Syarat Formal Gugatan - Baried, Rizky Ramadhan; Ridwan (Universitas Airlangga, 2024)
This article analyzes administrative effort in the relation of Article 62 Law 5/1986 with Article 75 Law 30/2014 and Article 2 Supreme Court Regulation 6/ 2018. The purposes are: 1) To analyze the position and urgency taken by administrative effort in the dismissal process examination by the chairman; and 2) To formulate the ideal formula for examining the formal requirements of the administrative lawsuit before being examined by the panel of judges. This article aims to provide a practical explanation of these norms. It is a normative juridical type with a statute, a conceptual, and a caseapproach. The results are: 1) Administrative effort is a formal requirement in filing a lawsuit related to competence, so the chairman can determine that the lawsuit is not accepted; 2) The dismissal process and the preparatory examination by analogy has similarities, therefore these examinations can be combined with the condition that in filing a lawsuit, the plaintiff is required to attach evidence of having taken administrative effort. It recommends that executive/legislature make regulations related to the procedural law for examining administrative effort, and for the supreme court to review the norms and practices of the dismissal process and the preparatory examination in relation to formal requirements for filing a lawsuit.